PENGEMBANGAN MODAL SOSIAL MAHASISWA LUAR JAWA DI UNIVERSITAS SLAMET RIYADI - Christy Damayanti GPH Dipo Kusumo (Universitas Slamet Riyadi, 2018)
Social capital is a capital that has important role in supporting individuals ininteracting with the society . The academic achievement and success of Slamet RiyadiUniversity students from outside Java is highly determined to develop social capital thataffect the level of trust, social interaction, and reciprocal quality. This study examines howstudents outside Java at Slamet Riyadi University Surakarta develop their social capital.As a qualitative research, this study obtained data through observation, interviews, anddisscusion group forums. The theory used in this research is the theory of social capitalfor education. The conclusion of this study is the factor that strongly hinder thedevelopment of social capital of students from outside Java at Slamet Riyadi UniversitySurakarta is the taste of food and language. Furthermore, to develop social capital isneeded role of institutional support of Slamet Riyadi University and communityinstitutions.Keywords: social capital, student, difference